PRISM (Polarized Radiation Imaging and Spectroscopy Mission): A White Paper on the Ultimate Polarimetric Spectro-Imaging of the Microwave and Far-Infrared Sky - Collaboration, PRISM; Andre, P; Baccigalupi, C; Barbosa, D; Bartlett, J; Bartolo, N; Battistelli, E; Battye, R; Bendo, G; Bernard, J; Bersanelli, M; Bethermin, M; et al. (2013)
PRISM (Polarized Radiation Imaging and Spectroscopy Mission) was proposed to ESA in response to the Call for White Papers for the definition of the L2 and L3 Missions in the ESA Science Programme. PRISM would have two instruments: (1) an imager with a 3.5m mirror (cooled to 4K for high performance in the far-infrared---that is, in the Wien part of the CMB blackbody spectrum), and (2) an Fourier Transform Spectrometer (FTS) somewhat like the COBE FIRAS instrument but over three orders of magnitude more sensitive. Highlights of the new science (beyond the obvious target of B-modes from gravity waves generated during inflation) made possible by these two instruments working in tandem include: (1) the ultimate galaxy cluster survey gathering 10e6 clusters extending to large redshift and measuring their peculiar velocities and temperatures (through the kSZ effect and relativistic corrections to the classic y-distortion spectrum, respectively) (2) a detailed investigation into the nature of the cosmic infrared background (CIB) consisting of at present unresolved dusty high-z galaxies, where most of the star formation in the universe took place, (3) searching for distortions from the perfect CMB blackbody spectrum, which will probe a large number of otherwise inaccessible effects (e.g., energy release through decaying dark matter, the primordial power spectrum on very small scales where measurements today are impossible due to erasure from Silk damping and contamination from non-linear cascading of power from larger length scales). These are but a few of the highlights of the new science that will be made possible with PRISM.